Online Teaching and Teachers’ Mental Burdens during the COVID-19 Pandemic - Syahputri, Veni Nella; Idami, Zahratul; Ismail, Nyak Mutia (International Conference on Multidisciplinary Research, 2020)
This study focused on outlining the psychological effects on teachers caused by the implementation of online teaching and learning during the COVID 19 pandemic. A descriptive qualitative approach was employed in conducting this study. There were 34 female teachers aged between 25-38 years old involved as respondents. The instrument used was a questionnaire sent through WhatsApp application. The data were analyzed using interactive analysis (data condensation, data display, and data verification). The results show that 34 respondents (100%) experienced uncertainty to their students; 58.8% (20 respondents) have physical pain and fatigue; 41.2% (14 respondents) experienced demotivation; 38.2% (13 respondents) tend to procrastinate their work; 67.7% (23 respondents) have bad time management; and 94.3% (32 respondents) experienced the feeling of isolation. Hence, it is suggested that educational institutions provide a care unit to handle any potential problems on teachers’ mental health. Keywords: mental burdens, online teaching, psychological health, psychological effects, and COVID-19 pandemic.